2021
DOI: 10.35848/1347-4065/ac10f2
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency improvement of AlGaN-based deep-ultraviolet light-emitting diodes and their virus inactivation application

Abstract: AlGaN-based ultraviolet light-emitting diodes (UV-LEDs) are key components for the inactivation of viruses. Highly efficient and high-power UV-LEDs, capable of inactivating viruses in a short time, are in demand. For this purpose, the growth technologies of n-type AlGaN contact layers were developed from two points of view: first, to decrease the resistivity of n-type Al0.62Ga0.38N by minimizing the electron compensation, resulting in electronic degeneracy with metallic conduction; second, to improve the light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The ternary alloy of III-nitrides, AlGaN, possesses large and adjustable direct band gaps ranging from 3.4 to 6.2 eV, and thus it becomes a promising material for detection and luminescence devices working in the ultraviolet (UV) wavelength. Peculiarly, the ability of killing most germs and viruses of AlGaN-based deep-UV diodes attracts increasing attention toward this material since the pandemic of COVID-19. The nontoxicity of AlGaN and miniaturization and stability of deep-UV diodes compared with traditional mercury lamps further promote demands and advances for AlGaN-related materials . Due to the absence of homoepitaxial substrates, heteroepitaxial substrates including sapphire, silicon carbide, and silicon , are currently applied for AlGaN growth.…”
Section: Introductionmentioning
confidence: 99%
“…The ternary alloy of III-nitrides, AlGaN, possesses large and adjustable direct band gaps ranging from 3.4 to 6.2 eV, and thus it becomes a promising material for detection and luminescence devices working in the ultraviolet (UV) wavelength. Peculiarly, the ability of killing most germs and viruses of AlGaN-based deep-UV diodes attracts increasing attention toward this material since the pandemic of COVID-19. The nontoxicity of AlGaN and miniaturization and stability of deep-UV diodes compared with traditional mercury lamps further promote demands and advances for AlGaN-related materials . Due to the absence of homoepitaxial substrates, heteroepitaxial substrates including sapphire, silicon carbide, and silicon , are currently applied for AlGaN growth.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Compared with conventional mercury discharge lamps, LEDbased DUV light sources can realize size reduction, lower energy consumption, and the reduced environmental risk. These advantages potentially meet the worldwide demand for devices that inactivate viruses [3] and sterilize water. [4] Although recent studies have reported external quantum efficiencies (EQEs) in excess of 10% for AlGaN-based LEDs with an emission wavelength of %280 nm, [5][6][7][8] further improvement is required for these devices to be used in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…These LEDs are considered replacements for the mercury lamps used in water and air sterilizations [1][2][3]. Deep-UV light with an emission wavelength below 290 nm can rapidly inactivate the deoxyribonucleic acid of virus and bacteria [4,5]; however, the light-emission efficiency (LEE) of deep-UV LEDs is considerably lower than that of low-pressure mercury lamps. The wall-plug efficiency of mass-produced deep-UV LEDs is a maximum of 10% because of the UV light absorption of the p-type gallium nitride (GaN) contact layer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%